2015
DOI: 10.1155/2015/379817
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Caspase-3 as a Common Therapeutic Target for Multineurodegenerative Disorders and Its Inhibition Using Nonpeptidyl Natural Compounds

Abstract: Caspase-3 has been identified as a key mediator of neuronal apoptosis. The present study identifies caspase-3 as a common player involved in the regulation of multineurodegenerative disorders, namely, Alzheimer's disease (AD), Parkinson's disease (PD), Huntington's disease (HD), and amyotrophic lateral sclerosis (ALS). The protein interaction network prepared using STRING database provides a strong evidence of caspase-3 interactions with the metabolic cascade of the said multineurodegenerative disorders, thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 47 publications
0
39
0
1
Order By: Relevance
“…The curcumin-caspase-3 interaction showed some amino acid residues that were Arg179, His237, Gln283, Ala284, Tyr338, Ser339, Trp340, Arg341, Phe381 and Ser343. Luteolin interacted with the Arg179, Ser236, Gln283, Tyr338, His237, Cys285, Tyr338, Ser339, Arg341, and Phe381 of caspase-3 [13]. Our study found that all anthocyanins except malvidin-3-Oglucoside bound to caspase-3 protein in Arg164, Tyr197, and Pro201.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…The curcumin-caspase-3 interaction showed some amino acid residues that were Arg179, His237, Gln283, Ala284, Tyr338, Ser339, Trp340, Arg341, Phe381 and Ser343. Luteolin interacted with the Arg179, Ser236, Gln283, Tyr338, His237, Cys285, Tyr338, Ser339, Arg341, and Phe381 of caspase-3 [13]. Our study found that all anthocyanins except malvidin-3-Oglucoside bound to caspase-3 protein in Arg164, Tyr197, and Pro201.…”
Section: Resultsmentioning
confidence: 50%
“…Some compounds have been identified as caspase inhibitor. They are rosmarinic acid, curcumin, luteolin, huperzine A, quercetin, resveratrol, bilobalide, EGCG, apigenin, berberine, and chitosan [13]. Flavonoid inhibits caspase-3 activity in MDA-MB-231 cells in in-vitro study [14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that flavonoids can function as specific activators or inhibitors of caspases 44,45 . Inhibitors against different caspases have been shown to rescue neuronal deaths in several experimental PD models 41,73 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated the involvement of caspases in inducing the death of DA neurons leading to PD pathogenesis 41,42 . Specifically, the activation of one of the downstream executioner caspases, caspase-3 has been associated with apoptotic cell death resulting in neuronal demise 43 .…”
Section: Differential Regulation Of Caspase-dependent Cellular Death mentioning
confidence: 99%
“…Quantum Mechanical Molecular Mechanical (QM/MM) docking strategy was used to determine the probable inhibitors of ahAR. Autodock4.2, a standalone software was used for the docking of all the selected compounds with the energy minimized modeled enzyme‐structures . Gasteiger type of charges and MMFF94 force field were used for the compounds and energy minimization of the ligands, respectively.…”
Section: Methodsmentioning
confidence: 99%